A Concise Review and Required Precautions for COVID-19 Outbreak in Diagnostic and Interventional Radiology. (22nd July 2020) - Kord, Ali; Rabiee, Behnam; Wang, Siwen; Rostami, Sara; Gaba, Ron C.; Xie, Karen L.
Abstract : A global outbreak of a novel coronavirus (COVID-19) pneumonia began in December 2019 in Wuhan, China. The World Health Organization (WHO) announced a pandemic on March 11, 2020. The rapid rise in the case numbers and mortality led to the saturation of hospitals in many countries. COVID-19 patients usually present with fever, fatigue, dry cough, and dyspnea. Given the shortage of diagnostic kits in many countries and very high sensitivity of computed tomography (CT) for diagnosis of COVID-19 in clinically suspicious patients, the chest CT has been implemented among the primary initial methods of diagnosis before the confirmatory laboratory tests. This puts radiologists and radiology staff on the front line of this alarming pandemic. This report summarizes chest CT findings of COVID-19 patients to facilitate diagnosis and reviews a list of necessary precautions and safety measures for diagnostic and interventional radiology personnel. These precautionary plans are extremely important to avoid contamination of the health-care providers, as well as cross-contamination between patients.